Generalized N* ideal closed sets in Nano N* ideal topological Spaces With Some Properties - Nabila I. Aziz; Taha H. Jasim (Tikrit Journal of Pure Science, 2022)
In this paper, we will study a new class of sets and said to be generalized N* ideal -closed sets in nano N* ideal topological spaces and its properties. Furthermore the relationships were introduced and notation